Efek Pemadatan Panas Pada Komposit Matrik Aluminium Diperkuat Alumina/Baggase Ash Densitas Dan Kekerasan - Wiryono, Sukanto; Ade Guna, Tegar; Rodika, Rodika; Wahyudi, Mego (Jurnal Inovasi Teknologi Terapan, 2024)
Baggase Ash waste in Indonesia is very abundant, so that in 2021 Indonesia exported 120 metric tons of bagasse to Yokohama, Japan. This study aims to determine the effect of volume fraction and sintering temperature on density and hardness of Aluminum (Al) Matrix Composite reinforced with Alumina (Al2O3) and Baggase Ash using powder metallurgy method. The mixing process of the composite material powders used a ball mill machine with ball ratio parameters of 10:1 and stirring time for 2 hours at a rotating speed of 90 rpm. The parameters set are mechanical fusion for 2 hours, a compaction pressure of 6000 Psi, a sintering temperature varied by three kinds of 550 °C, 580 °C, 610 °C with a holding time duration of 15 minutes, and with three kinds of aluminum matrix fractions, namely 95%, 90%, 85% with alumina alloy reinforcement and baggase ash is 5%, 10%, 15%. Density testing was carried out based on Archimedes' law with reference to the ASTM B962-17 standard, while the hardness test was based on the Brinell portable hardness test with ASTM E110-14 standard. The largest density number is obtained at 5% reinforcement content, that is 2,228 g/cm3 and the largest hardness number is obtained in the 5% sample, that is 41.6 HB.